(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2016)
The communal politics of the Punjab was very complicated because here lived three communities – the Hindus, the Muslims and the Sikhs. According to the census of 1941, there lived 13 Sikhs, 30 Hindus and 57 Muslims in the Punjab. In the elections of 1937, Muslim League was defeated badly. Jinnah wanted cooperation of the Punjab Muslims because they were to majority in the Punjab. For this reason he decided to make an agreement with Sikander Hayyat Khan. In Lucknow in 1937 an agreement took place between Mohammed Ali Jinnah and Sir Sikander Hayyat Khan which is known as Sikander – Jinnah Pact. The pact is considered to be the diplomatic victory of Mr. Jinnah. This pact also consolidated the position of the Muslim League and enhanced the popularity of Mr. Jinnah but still Muslim League was not content. It passed the resolution of Independent Pakistan on March 23, 1940. Crips mission came to India but the Congress, the Muslim League and the Hindu Maha Sabha rejected its recommendation. In the assembly election of the Punjab in 1945-46, Muslim League won more seats than any other party, but it could not get absolute majority. Then a coalition government was formed in Punjab, but the Muslim League started communal riots. At last according to the recommendations of Lord Mount-batton India and Pakistan were partitioned.